Diving literature - Zimmermann, W. (2010)
This is the world`s largest diving literature reference base. It contains over 3500 references to books, articles and other publications related to springboard and platform diving. The database is regularly updated. You can easily open our database and search for a subject or author, in several languages. Our database is presented as a PDF file. You can print one or all pages of the database using the menu`s. It takes about one minute before the database appears, after you press enter.